DIRECTIONS FOR IMPROVING INTERNAL AUDIT IN COMMERCIAL BANKS - Oromidinov, Muzaffar (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This study investigates internal auditing in commercial banks and offers recommendations for improvement. It emphasizes the importance of internal audits in regulatory compliance, asset protection, and performance enhancement. Key challenges include governance, risk assessment, technology integration, and continuous training. Recommendations include active board participation, improved risk assessment, technology integration, and continuous training programs. Overall, a strong internal audit function is crucial for operational excellence and stakeholder trust.